Embodiment of Ancestral Spirits, the Social Interface, and Ritual Ceremonies: Construction of the Shamanic Landscape among the Daur in North China - Qu, Feng (Religions, 2021)
The case study in this paper is on the Daur (as well as the Evenki, Buriat, and Bargu Mongols) in Hulun Buir, Northeast China. The aim of this research is to examine how shamanic rituals function as a conduit to actualize communications between the clan members and their shaman ancestors. Through examinations and observations of Daur and other Indigenous shamanic rituals in Northeast China, this paper argues that the human construction of the shamanic landscape brings humans, other-than-humans, and things together into social relations in shamanic ontologies. Inter-human metamorphosis is crucial to Indigenous self-conceptualization and identity. Through rituals, ancestor spirits are active actors involved in almost every aspect of modern human social life among these Indigenous peoples.